Forward dynamic simulation of Japanese macaque bipedal locomotion demonstrates better energetic economy in a virtualised plantigrade posture - Hideki Oku (Nature Portfolio, 2021)
Oku, Ide and Ogihara use forward dynamic simulation to virtually manipulate the foot posture of the Japanese macaque from a digitigrade to plantigrade posture for bipedal locomotion. This postural shift results in greater energetic economy despite the macaque not having anatomy adapted for bipedal movement. Structural changes in the foot are likely a key component of the acquisition of human-like bipedal locomotion.